Tratamento de sistemas abertos via reservatórios térmicos bosônico e fermiônico - Araújo, Dannilo Iágor Evangelista de (2019)
We developed this work at the moment with the objective to resolver the master equation for both thermal reservoir: bosonic and fermionic, as well as the master equation in reservoirs of vacuum and of Fock compressed . the bosonic thermal reservoir is modeled by a collection of coupled harmonic oscillators and the fermionic reservoir by a collection of two-level atoms. We made use of the Jaynes-Cummings model and the Bohr, Bohr-Markov and Markov approaches. In the end we discussed the application to the master equation for two distinct phenomena, Cooling by Heating (CBH) analyzing average energy graphs to the atomic system versus number of photons, and the average energy of the bosonic system as a function of the mean number of phonons, we observed the negative temperature in the absolute scale due to the inversion of population of states in function of cooperativity, we also analyzed a signature of negative response in a three level system interacting in a optical cavity, that comes as a result of decrease in the output field intensity when the input field intensity is increased.